Design of a CMOS-based microwave active channelized bandpass filter - Jarjar Mariem; Pr. El Ouazzani Nabih (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
A two-branch microwave active bandpass filter is designed through the channelized filtering technique as well as the transversal concept. Both the main and the auxiliary branches, connected without power dividers/combiners, rely on C-coupled active third order Chebyshev bandpass filters. A lumped element signal delay circuit is also introduced in the main channel. Active inductors based on the gyrator-C topology, are involved in the Chebyshev filters’ structure. CMOS-based Operational Transconductor Amplifier (OTA) circuits are the building blocks of these inductors. The proposed active transversal channelized filter produces an elliptic narrow band response, centered at 1.13 GHz. Simulation results, obtained by means of the PSPICE code according to the 0.18 μm TSMC MOS technology, indicate excellent performances illustrating good impedance matching, low insertion losses and high selectivity. Finally, the noise analysis shows that the filter has a low noise figure in the bandwidth.